ANALYTICAL STUDY OF ISSUES AND CHALLENGES OF WORKING WOMEN REGARDING SEXUAL HARASSMENT AT WORKPLACE - Bibi, Chand; Rishi, Kamlesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Working women are aware of sexual harassment in different areas like private place, workplace etc. This article presents a comprehensive analysis on Indian laws governing assault, misbehavior and sexual harassment of working women at workplace. And furthermore, it is mentioned in this article as to how the Prevention of Sexual Harassment of Women at Workplace is read as per the Criminal Law (Amendment) Act, 2013 under various sections of the law relating to sexual harassment of working women at workplace which means to prevent the offenders from assaulting, using criminal force with the intent to disrobe, stalking, peeping and other such crimes against working women. It is undoubtedly a fact that women have to face severe abuse and assault by human beings since ancient times. To prevent and control such crimes, laws have been made by the government, but a lot of conditions have been put in place for the implementation of such laws and great difficulties have to be faced in implementing these laws. This article examines the problems and challenges faced in protecting women from sexual harassment at workplace in relation to the Sexual Harassment of Women (Prevention, Prohibition and Redressal) Act, 2013.